2019
DOI: 10.3389/fnhum.2019.00332
|View full text |Cite
|
Sign up to set email alerts
|

Low or High-Level Motor Coding? The Role of Stimulus Complexity

Abstract: Transcranial magnetic stimulation (TMS) studies have shown that observing an action induces activity in the onlooker's motor system. In light of the muscle specificity and time-locked mirroring nature of the effect, this motor resonance has been traditionally viewed as an inner automatic replica of the observed movement. Notably, studies highlighting this aspect have classically considered movement in isolation (i.e., using non-realistic stimuli such as snapshots of hands detached from background). However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…However, Amoruso and Finisguerra (2019) argued that motor resonance only reflects an automatic replica of observed actions, if observed in isolation, but that it can be modulated by topdown inputs in presence of contextual cues. Our results support this hypothesis: Weight-driven motor resonance was present when weight expectations were never challenged (control group), but turned out to be suppressed when a size-weight mismatch was introduced (baseline group).…”
Section: Discussionmentioning
confidence: 99%
“…However, Amoruso and Finisguerra (2019) argued that motor resonance only reflects an automatic replica of observed actions, if observed in isolation, but that it can be modulated by topdown inputs in presence of contextual cues. Our results support this hypothesis: Weight-driven motor resonance was present when weight expectations were never challenged (control group), but turned out to be suppressed when a size-weight mismatch was introduced (baseline group).…”
Section: Discussionmentioning
confidence: 99%
“…To build up their predictions, participants were instructed to carefully pay attention to both aspects of the scene: the agent's hand preshaping and the contextual information in which the action was embedded. It is worth noting that, in keeping with previous studies (11)(12)(13), correct responses were defined by hand configurations in terms of precision vs. power grips, not by the context. Thus, when the participants observed a precision grip of a cup, "to drink" was the correct response irrespective of the breakfast or cleaning scenario.…”
Section: Experiments 1: Spatial Frequency Contributions To Action Compmentioning
confidence: 95%
“…The current study builds on previous evidence showing that corticospinal excitability (CSE) in the motor system becomes differentially modulated depending on the context in which an action is observed (for a review, see ref. 13). Briefly, in a series of studies, we found that the observation of movement kinematics occurring in congruent contexts (i.e., reaching-to-grasp a cup full of coffee with a precision grip) increases motor CSE facilitation, while its observation in incongruent contexts (i.e., reaching-to-grasp an empty cup with a precision grip) results in decreased motor facilitation compared to observing the same kinematics in neutral contexts.…”
Section: Significancementioning
confidence: 96%
“…Indeed, dealing with social interactions in an effective way often requires the ability to anticipate others' behavior, predicting their intentions from observing their movements. Movement kinematic information, however, may be ambiguous in many (if not most) social situations [8,9]. Thus, a social observer needs to integrate this sensory evidence with knowledge of past experiences aiming at the same goal or with contextual cues facilitating action prediction [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%